Chapter Chronotopes of Affectivity in Literature. On Melancholy, Estrangement, and Reflective Nostalgia - Salmon, Laura (Biblioteca di Studi Slavistici, 2015)
Basing our analysis on the concepts of 'emotion', 'feeling', and 'mood' as defined by data from the cognitive sciences, we argue that human emotions are both universal and intrinsically linked to literary and artistic chronotopes. In her study of 'reflective' and 'restorative' nostalgia, Svetlana Boym (2001) shows that 'nostalgia' itself represents pure ambivalence that takes on a particular shape in response to the mood, thoughts, and psychological state of the author. Its ultimate expression might assume the form of either monological ideology or of paradoxical existential emotion. It is this second type of nostalgia that we can link most closely link to understandings of both 'melancholy' and 'identity' or 'self-consciousness'. Brooding and melancholic toska is shared by persons who suffer from what we might call 'existential ambivalence'; these persons are 'mercurials' in the terminology of Yuri Slezkine (2004). Within the field of Russian literature, this 'mercurial' sense of melancholy is particularly well developed.